2018
DOI: 10.18203/2320-1770.ijrcog20180454
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the acceptance and awareness of permanent method of family planning

Abstract: Background: Among developing countries, India holds the second place in being the most populated country accounting to 1.3 billion. This addresses the need for effective population control by implementing various family planning and contraceptive services thereby improving the quality of life. Our study aims at assessing the factors influencing the awareness and acceptance of permanent method of family planning.Methods: This is a questionnaire based cross sectional study carried out in A.J. institute of Medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…The result of this study revealed that being in the age category of 30-39 years had an increased intention to use vasectomy as a contraceptive method as compared to the age category of 20-29 years. This finding is supported by studies conducted in India and Nepal [17,31]. Another study conducted in Indonesia also showed that the age of the respondent which was found between 30-39 had a significant relationship with intention to vasectomy [32].…”
Section: Plos Onesupporting
confidence: 65%
“…The result of this study revealed that being in the age category of 30-39 years had an increased intention to use vasectomy as a contraceptive method as compared to the age category of 20-29 years. This finding is supported by studies conducted in India and Nepal [17,31]. Another study conducted in Indonesia also showed that the age of the respondent which was found between 30-39 had a significant relationship with intention to vasectomy [32].…”
Section: Plos Onesupporting
confidence: 65%
“…Female sterilization is performed at young ages, with 43% of currently sterilized women sterilized before the age of 25 years [29]. Since young women are more likely to express permanent contraception regret, expanding choice for highly effective, reversible contraception safe to use during breastfeeding could allow couples to delay female sterilization and avert permanent contraception regret [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…The study's projected sample size was determined based on the predominant factor influencing NSV acceptance, as identified in a prior cross-sectional study conducted in Mangalore by Shettian and Ajila [9] in 2018, where the observed proportion was 27.8%. Calculations were performed with a relative precision of 9% and a confidence level of 95%, resulting in an estimated sample size of 95 participants.…”
Section: Sample Size and Samplingmentioning
confidence: 99%